Effect of water pressure and temperature on the perform-ance of a desalination reactor - Dwibowo, Dany Alvian; Mugisidi, Dan; Heriyani, Oktarina; Alamsyach, Rizky; Amin, Syahrul (Jurnal Polimesin, 2025)
The crisis of clean water availability has become increasingly critical due to rapid population growth and environmental degradation. One strategic approach to address this challenge is to implement seawater desalination, which provides an abundant, sustainable water source. However, conventional methods remain limited in terms of energy efficiency. This study aims to analyze the effect of pressure and temperature variations on the performance of a large-capacity desalination reactor with an 8000-liter tank. Two configurations were experimentally tested: (1) an air-circulation system that relies on static heating assisted by an axial fan to enhance convection, and (2) a sealed system operating under low-pressure conditions to reduce the boiling point of water, equipped with active hot-water circulation. Data collection was carried out over 27 hours of operation, with the observed parameters including water temperature, partial pressure, relative humidity, and evaporation volume. The experimental results showed that the sealed configuration delivered superior performance, with an evaporation rate 16.64% higher than that of the air-circulation variant. The volume of water successfully evaporated in the sealed system reached 20.12 liters, whereas in the air-circulation system it was only 17.25 liters. This increase in efficiency is attributed to the pressure-reduction effect, which enhances the vapor pressure difference while facilitating uniform heat distribution through active water circulation. This study emphasizes that controlling pressure and temperature is key to improving the effectiveness of the desalination process, thereby supporting the Development of more energy-efficient and sustainable clean water supply technologies.